Herman Kruk (1897-1944) jako organizator i dyrektor biblioteki getta wileńskiego. Szkic do obrazu bibliotekarstwa żydowskiego w Polsce - Gruszka, Zbigniew (Acta Universitatis Lodziensis. Folia Librorum, 2010)
The author presents the result of biographical research conducted among of Herman Kruk, a librarian, political and social activist, and active creator of the B. Grosser Library in Warsaw and the Vilna Ghetto Library. Information gathered led to a fuller presentation of his achievements, especially thanks to the materials and autobiographical memoirs, published recently.